Peran Guru dalam Pelaksanaan Manajemen Kebersihan Menstruasi (MKM) di Lingkungan Sekolah Dasar Wilayah Pare - Dina Zakiyyatul Fuadah; Laella Chabiba (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Menstrual Hygiene Management (MHM) is the management of hygiene and health during women's menstrual period. One of the factors that influence Menstrual Hygiene Management (MHM) is the role of the teacher. Teachers play a role in equipping students with knowledge about hygiene, facilitating proper toilets and how to maintain their reproductive organs, this will have a positive impact on students in elementary schools. This study aims to determine the description of the role of teachers in implementing the menstrual hygiene management (MHM) program at Elemantary School Pare area. The research design used Descriptive Analytic, with sampling technique using Purposive Sampling obtained a sample of 40 respondents. Data collection using questionnaire sheet, data processed with descriptive statistical test. Based on the results of research in 6 (six) Elemantary School in the Pare Region on the role of teachers in the implementation of Menstrual Hygiene Management (MHM), almost all data were found to be in the good and sufficient category, especially in the indicator as the role of facilitator (79.30) and supervisor (76.87). From the results of the data, the role of facilitator and supervisor is the highest because the facilities in several schools have met the criteria for Menstrual Hygiene Management (MHM) and the observations of teachers at school to female students have been carried out well, but there are still roles that score the lowest, namely educator (63.75) because some respondents have never received counseling on Menstrual Hygiene Management (MHM) and still lack of education. Primary school teachers are advised to take part in training to increase knowledge about menstrual hygiene management (MKM)